Markets of Electricity and Heat in the Russian Far East: 30 years of Transformation - Dyomina Olga; Naiden Svetlana (E3S Web of Conferences, 2023)
The paper studies transformations in electricity and heat markets of the Russian Far East in 1980-2022. The timeline can be broken down into 4 periods of development in the region: pre-reform (1980-1991), economic reform (1992-1999), electricity market reform (2000-2011), and heat market and institutional reform (2012-2022). Development of electricity and heat markets happened during a period of demand and supply imbalance. High costs of energy supply, deficit of energy, and issues with fuel supply in the pre-reform period worsened in the next period. During economic reforms sharp drop in subsidies, rising costs of energy resources, non-payments for energy, lack of investments caused a massive energy crisis in the region despite sharp drop in demand. From the beginning of 2000s the economy started to recover, with demand of electricity growing. During electricity market reforms the Russian Far East was consolidating assets in electricity and heating industries, forming distinct market segments: non-price zone of wholesale market and retail markets of isolated energy systems. The 2000s continued to be plagued by issues of high deprecation of generators, lack of mass investments for modernization, and high energy prices for consumers. The latter required application of several measures after 2012: special decrees of the President and the Government of Russia to construct new electric power plants, modernize and construct CHP power plants; to provide ready infrastructure for residents of the advanced development territories, financed by the state; the state co-financing network infrastructure and connections for priority investment projects; bringing the tariffs for industrial consumers of certain territories of the region to the level of country average.